Effect of different surface treatments on bioactivity of porous titanium implants. Issue 3 (March 2019) - Todea, M.; Vulpoi, A.; Popa, C.; Berce, P.; Simon, S.
Highlights: Medical grade Ti6Al7Nb alloy implants manufactured by Selective Laser Melting (SLM). Heat treatment, chemical treatment, and impregnation with bioactive materials. Treatments effect on bioactivity of SLM derived implants tested in vitro. XRD, SEM/EDX, XPS analyses. Abstract: The work aims to characterize the structure and to evaluate in vitro the effect of different surface treatments on the bioactivity of medical grade Ti6Al7Nb alloy implants manufactured by selective laser melting. In order to improve the bioactivity of these samples, they were subjected to heat treatment, chemical treatment, and impregnation with bioactive materials. To evaluate the apatite forming ability, the samples were immersed in simulated body fluid solution) and characterized before and after immersion by scanning electron microscopy, X-ray diffraction and X-ray photoelectron spectroscopy. The composition and the texture of the surfaces after the applied treatments have a selective effect on apatite layer development on the surface of samples.